2008
DOI: 10.1016/j.websem.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Discovering shared conceptualizations in folksonomies

Abstract: Social bookmark tools are rapidly emerging on the Web. In such systems users are setting up lightweight conceptual structures called folksonomies. Unlike ontologies, shared conceptualisations are not formalised, but rather implicit. We present a new data mining task, the mining of all frequent tri-concepts, together with an efficient algorithm, for discovering these implicit shared conceptualisations. Our approach extends the data mining task of discovering all closed itemsets to three-dimensional data structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 53 publications
0
48
0
5
Order By: Relevance
“…Aschke et al [5], observed that many factors limit WordNet from extensive coverage of Del.icio.us tags. WordNet only provides coverage of English language and is composed of static body of words while Del.icio.us has tags from different languages.…”
Section: Statistical and Mathematical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aschke et al [5], observed that many factors limit WordNet from extensive coverage of Del.icio.us tags. WordNet only provides coverage of English language and is composed of static body of words while Del.icio.us has tags from different languages.…”
Section: Statistical and Mathematical Techniquesmentioning
confidence: 99%
“…& Statistical/ Mathematical Approaches-Clustering techniques keeping in view only tagging information and tag co-occurrence to find out semantically related sets of tags and resources, out of folksonomy, are achieved in [12] Flickr clusters 5 . Such techniques require only statistical analysis tags and they lack semantic information.…”
Section: Clusteringmentioning
confidence: 99%
“…An approach for making explicit the semantics behind the tag space through mapping folksonomies to existent ontologies are presented by Specia et al [17]. Jaschke et al [18] defined a new data mining task, the mining of frequent tri-concepts, and presented an efficient algorithm to discover these implicit shared conceptualizations. Furthermore, there are many research works focusing on ontology learning from folksonomies.…”
Section: Related Workmentioning
confidence: 99%
“…Views are used in this case, since that blogs are not typically available on collaborative tagging websites, and as such the tags provided by bloggers suffer from the vocabulary problem and cannot be adequately used as a shared index. Finally in [17], the goal is to provide a seamless navigation between tag spaces, while the the work presented in [6] merges the areas of formal concept analysis and association rule mining to discover shared conceptualizations that are hidden in folksonomies.…”
Section: Unified Tag Spacesmentioning
confidence: 99%